A Developed Network Layer Handover Based Wireless Networks - Sadiq, Ali Safa; Kamarulnizam, Abu Bakar; Ghafoor, Kayhan Zrar; Lloret, Jaime; Fakhreldin, Mohammed Adam Ibrahim (UMP Publisher, 2015)
This paper proposes an Advanced Mobility Handover (AMH) scheme based on Wireless Local Area Networks (WLANs) by developing a network layer handover procedure which triggers messages to be sent to the next access point. The proposed AMH scheme performs the network handover process, which is represented by binding update procedure in advance during the time mobile node is still connected to the current AP in the link layer. Furthermore, a unique home IPv6 address is developed to maintain an IP communication with other corresponding nodes without a care-ofaddress during mobile node$'$s roaming process. This can contribute significantly to reducing network layer handover delays and signaling costs by eliminate the process of obtaining a new care-of-address and processing the handover of network layer in advance while the mobile node is still communicating with the current access point. Eventually, the conducted OMNET++ simulated scenario shows that the proposed AMH scheme performs the best in terms of reducing the handover delay as compared to the state of the art.